ENGLISH WITH INDONESIA TASTE DOMINANT CULTURE SHIFT TO LOCAL CULTURE - Yamin, Moh. (LET: Linguistics, Literature and English Teaching Journal, 2014)
English is not only the language that should be learned and mastered as the tool of communication, but it also should be understood as the language that has its own world. Although English is not the mother tongue of Indonesia, but it has been the cultural part of Indonesia when the Indonesian people use it as the medium of interaction. That is why, English as the life part of Indonesia should have the spirit of Indonesia. The cultural values that come from England, America or other countries using English as the mother tongue should be deleted. Making English for Indonesian people is a must. It means that what the people learn from English is not the culture, but the language itself. Separating the English from its own culture and bring it into Indonesian culture is a new way without forgetting the knowledge of English culture for enriching the language culture knowledge. Many Indonesian people use English as the medium of communication as if they are English people, such as their performance, gesture, behavior, and so forth. This case creates the stigma that English has destructed the local culture, whereas learning and using English is not for that, but for medium of interaction